Behring Sea arbitration [electronic resource] : appendix to counter-case of Her Majesty's government. - Behring Sea Tribunal of Arbitration.; United States.; Great Britain. ([S.l. : s.n., 1893)
The case, involving Great Britain and the United States, was heard before the Behring Sea Tribunal of Arbitration, in 1893. Tables. Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 14434-14436. "Vol. I." Electronic reproduction. Mode of access: Internet. 44